Temporary migration policies and welfare of the host and source countries : a game-theoretic approach - Slobodan Djajić; Michael S. Michael (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper examines the interaction between migration policies of the host and source countries in the context of a model of guest-worker migration. For the host, the objective is to provide low-cost labor for its employers while avoiding illegal immigration. It optimizes over these objectives by setting the time limit of a guest-worker permit. The source country seeks remittance flows and return migration by offering fiscal benefits to returnees. Within this framework, we solve for the Nash equilibrium values of the migration policy instruments and compare them with the ones that emerge in a cooperative setting.
Keywords: F22; 330; temporary migration; remittances; migration policy; Internationale Arbeitsmobilität; Saisonarbeitskräfte; Migrationspolitik; Spieltheorie; Nash-Gleichgewicht; Wohlfahrtseffekt; Theorie